PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IX SMPN 7 PARIAMAN - Liza, Fasra; Rahmi, Rahmi; Edriati, Sofia (Pendidikan Matematika, 2013)
The background of this research is the studentsâ mathematical concept understanding that is still low. The purposes of research are to know how the development of the studentsâ mathematical concept understanding is and to know whether the studentsâ mathematical concept understanding by applying the cooperative learning model of Think Pair Share type with quiz is better than that by using the conventional learning. The type of research is an experimental research with Random to Subject design. The population of research is the grade-IX students of SMPN 7 Pariaman of the year 2013/2014. The technique of sampling is applied randomly and the chosen samples are IX.2 as an experimental class and IX as a control class. The instruments used in this research are quiz and final tests of mathematical concept understanding. The form of tests used is essay and the test reliability is 0.89. The technique of data analysis is t-test of one side with MINITAB. Based on the analysis of data, it is known that both sample classes are distributed normally and homogenous at Î± level of 0.05. The hypothesis tests are indicated that P-value is similar to 0.028, meaning less than 0.05, so that the hypothesis of this research is accepted. Then, it can be summarized that the studentsâ mathematical concept understanding by applying the model of cooperative learning of Think Pair Share type with questionnaires is better than that by using the conventional learning with trust level of 95%. Quiz look at the development of indikators to classify objects according to the nature of certain properties cantained in the quiz I, III, and IV quiz. Quizzes I progress indikator is 86,22%, quiz III percentage progress indikator is 88,89% and the percentage development indikator quiz IV 90,97%.